2011
DOI: 10.2174/156802611794480864
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic-Pharmacokinetic Integration as a Guide to Medicinal Chemistry

Abstract: A primary objective of pharmacokinetic-pharmacodynamic (PKPD) reasoning is to identify key in vivo drug and system proper¬ties, enabling prediction of the magnitude and time course of drug responses under physiological and pathological conditions in animals and man. Since the pharmacological response generated by a drug is highly dependent on the actual system used to study its action, knowledge about its potency and efficacy at a given concentration or dose is insufficient to obtain a proper understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…However, it is increasingly being recognized that successful implementation of PKPD reasoning in early drug discovery could have at least as much impact on the overall efficiency and success of pharmaceutical research as comparable investments in late-stage modelling and simulation (7,8), and this is now increasingly being reduced to practice to guide medicinal chemistry programs (11). This conclusion derives from the assertion that arguably the most significant challenge facing the pharmaceutical industry is compound attrition, resulting from the failure of preclinical efficacy and safety model data to translate into human proof-of-mechanism/concept studies (9,10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is increasingly being recognized that successful implementation of PKPD reasoning in early drug discovery could have at least as much impact on the overall efficiency and success of pharmaceutical research as comparable investments in late-stage modelling and simulation (7,8), and this is now increasingly being reduced to practice to guide medicinal chemistry programs (11). This conclusion derives from the assertion that arguably the most significant challenge facing the pharmaceutical industry is compound attrition, resulting from the failure of preclinical efficacy and safety model data to translate into human proof-of-mechanism/concept studies (9,10).…”
mentioning
confidence: 99%
“…To this end, it has been suggested that PKPD modelling and simulation can play a significant role in early preclinical drug discovery (11) and provide a framework for translational research which links, in a quantitative manner, the interactions between a drug or combination of drugs, pharmacological targets, physiological pathways and, ultimately, integrated disease systems (12). However, historically, the discipline focusing on integrating PKPD has been data driven, with strong emphasis on (bio-)statistical approaches such as non-linear mixed effect (populationbased) modelling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When feasible, the systems or PBPK model developed in early discovery should be incorporated into the pharmacology understanding. Next, translational pharmacology becomes essential at the transitional phase between candidate selection and FIH (8). At this stage, the scaling of the PK and PD from animals to human using a model-based approach with no adverse effect level (NoAEL) and minimally anticipated biological effect level (MABEL) (if needed) considerations is used to guide decisions on the starting as well as escalating dose decisions in the FIH study.…”
Section: Depicted Inmentioning
confidence: 99%
“…However, it was also recognized that in order to tackle Phase II attrition additional steps are required. One such step may include implementation of PK/PD reasoning in early drug discovery [5,6] since by addressing attrition as early as possible, before the major clinical costs are incurred, the greatest potential efficiencies can be realized [7,8].…”
mentioning
confidence: 99%